A synonymous (c.3390C>T) or a splice‐site (c.3380‐2A>G) mutation causes exon 26 skipping in four patients with von Willebrand disease (2A/IIE). Issue 7 (15th July 2013) - Pagliari, M. T.; Baronciani, L.; Garcìa Oya, I.; Solimando, M.; La Marca, S.; Cozzi, G.; Stufano, F.; Canciani, M. T.; Peyvandi, F.
Summary: Introduction: We characterized four unrelated patients with von Willebrand disease type 2A/IIE, sharing the same von Willebrand factor (VWF) in‐frame deletion (p.[P1127_G1180delinsR];[=]) resulting from exon 26 skipping (Δ26). Objectives: To identify the VWF mutations and how they caused the mRNA splicing alteration, to evaluate the deletion by in vitro expression studies, and to assess whether or not the heterogeneity of the patients' phenotype might be related to a different degree of expression of the deleted subunit in patient plasma VWF. Methods: Sequence analysis was performed with patient genomic DNA and platelet mRNA. Semiquantitative RT‐PCR was also carried out to compare the expression of the wild‐type (WT) and Δ26 alleles in the four patients. In silico analysis was performed with prediction splicing programs. Expression studies were performed to evaluate mutant recombinant VWF (rVWF) (Δ26 and Δ26/WT) as compared with WT rVWF. Results: Three patients shared the synonymous single‐nucleotide substitution (SSS) c.[3390C>T];[=], whereas the novel mutation c.[3380‐2A>G];[=] was present in the fourth patient. Semiquantitative RT‐PCR of platelet mRNA revealed a different ratio of the WT and Δ26 alleles in the patients, consistent with the different VWF:FVIIIB values present in patient plasma. Expression studies confirmed reduced VWF–FVIII binding of rVWF‐Δ26/WT. Conclusions: SSS can induce alternative splicing, and those like c.3390C>T, which impact on the poorly conserved splicing regulatory elements, are difficult to predict, so that their role can be evaluated only by mRNA analysis. Moreover, these mutations seem to have different effects on the efficiency of alternative splicing, producing heterogeneous VWF variants among the four patients.